THE IMPACT OF DEFERRED TAX EXPENSE AND TAX PLANNING TOWARD EARNINGS MANAGEMENT AND PROFITABILITY - ROCKY ALFIAN BUNACA; NURDAYADI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2019)
The aim of this research is to analyze the impact of Deferred Tax Expense and Tax Planning toward Earnings Management and Company’s Profitability. The sample of this research are taken from 24 companies from Consumer Goods Sector that listed in Indonesia Stock Exchange from 2013 – 2017. The variables of this research are Deferred Tax Expense and Tax Planning as Independent Variables, Earnings Management as Intervening Variable, and Company’s Profitability as Dependent Variable. This research use Path Regression Analysis to analyze the role of Intervening Variables in influence other variables. The result of this research, it is found that Deferred Tax Expense has a significant influence toward Earnings Management, but has no influence toward Company’s Profitability. Tax Planning has no significant influence to Earnings Management, but has a significant influence toward Company’s Profitability. It also found that Earnings Management as intervening variable strengthen the influence from Deferred Tax Expense toward Company’s Profitability, but weaken the influence from Tax Planning toward company’s profitability.